CORPORATISM IN WESTERN EUROPE: CURRENT STATE AND PROSPECTS FOR EVOLUTION - Р. Ja. Feldman (MGIMO University Press, 2018)
The article conducts a political analysis of the Western European institutions of corporatism. The main task of the author is the study of the policy of harmonizing the interests of labor and capital (trade unions and employers’ associations), which is implemented in countries such as the UK, Germany, France, Italy, Norway, Sweden, Denmark etc. Dynamics of political processes unfolding in the space of Western Europe, suggests that the mechanisms of articulation and political representation of social and labour interests have significantly transformed over the past 30 years. The use of institutional and systemic approaches along with the empirical methods, leads to the conclusion that the most developed European countries are moving from the classical model of corporatism to a more pluralistic forms of interaction between the state, labour and capital. Social partnership as an instrument of collective bargaining between employees and employers is displaced from the political sphere to the sectoral and organizational levels. The typical institutions of democratic corporatism (tripartite commissions, socio-economic councils, etc.), who played a crucial role in rebuilding post-war Europe, become rudimentary organs of the national political systems. In addition, there is a tendency to weaken the political influence of trade unions, who successfully struggled for the satisfaction of collective demands of workers in the beginning of XX century. Large multinational companies prefer to influence the political decision-making centers autonomously, ignoring the associative membership in the guild organizations. As a consequence, corporatist bargaining is being replaced by direct and indirect lobbying, Government Relations and election fundraising. When accounting for identified trends, the author presents a hypothesis that the evolution of corporatism in Western Europe will lead to its gradual degeneration. Taking into account the identified trends, the author presents a hypothesis that the evolution of corporatism in Western Europe leads to its gradual degeneration.